2001
DOI: 10.1177/101053950101300107
|View full text |Cite
|
Sign up to set email alerts
|

Sero-epidemiology and Risk Factors of Positive Hepatitis B Surface Antigen amongst Chinese Adolescents

Abstract: This paper reports the prevalence rate of hepatitis B antigen (HBsAg) amongst the Hong Kong Chinese adolescents (age 11 to 19), and the risk factors associated with HBsAg positive. The study is cross sectional and 1,580 students were randomly selected from 12 secondary schools in four regions of Hong Kong. For those subjects who agreed to participate and were randomly selected, their blood was tested for HBsAg and anti-HBs. The overall prevalence of HBsAg positive was reported to be 5.8% (7.9% in male and 4.1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
3
5
1
1
Order By: Relevance
“…In accordance with previous reports, 10,22,33,34 boys were more likely to have chronic infection in comparison to girls, in the present study. The reason for the sex difference remains unclear.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In accordance with previous reports, 10,22,33,34 boys were more likely to have chronic infection in comparison to girls, in the present study. The reason for the sex difference remains unclear.…”
Section: Discussionsupporting
confidence: 94%
“…27,30 Thus, measuring the aminotransferase levels remains the most common and convenient way to determine liver infl ammation in patients with chronic HBV infection, but the relationship may be better established by serial observations rather than by a single examination of aminotransferase levels. 31,32 In accordance with previous reports, 10,22,33,34 boys were more likely to have chronic infection in comparison to girls, in the present study. The reason for the sex difference remains unclear.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, living in a rural area was not found as a risk factor for transmission of hepatitis B. Some studies have reported that there was a significant seropositivity difference between rural and urban regions 20, 26. There are 56 ethnic groups in China and the lifestyle of the minority ethnic population is considerably different from the Han majority ethnic population.…”
Section: Discussionmentioning
confidence: 95%
“…Studies from China, Thailand, Malaysia, Hong Kong, Korea and Singapore have all shown the effectiveness of routine infant hepatitis B vaccination 19,31,42–45 . These studies have reported marked decreases in the HBV carrier rate and HBsAg seropositivity among children and adolescents born since the introduction of the infant vaccination program in their country, compared with children and adolescents born prior to its implementation.…”
Section: Prevention Of Hepatitis B Virusmentioning
confidence: 99%